Savings from the introduction of BPaL and BPaLM regimens at the country level - C. Auer; A. Gupta; C. Malbacius; A. Ghafoor; Y. Kock; O. Medvedieva; P. Hanlon; P. Steinmann; S. Juneja (IJTLD Open)
BACKGROUND: In 2022, the WHO recommended the 6-month regimens BPaL (bedaquiline + pretomanid + linezolid) and BPaLM (BPaL + moxifloxacin) as treatment options for most forms of drug-resistant TB. SLASH-TB estimates the cost-saving and cost-effectiveness for the healthcare system and patients when a country switches from current standard-of-care treatment regimens to BPaL/BPaLM. METHODOLOGY: Country data from national TB programmes (NTP) are used to calculate the costs for all regimens and treatment outcomes. Where BPaL/BPaLM is not currently used, clinical trial outcomes data are used to estimate cost-effectiveness. DALYs are calculated using the Global Burden of Disease (GBD) database. RESULTS: We present the results of four countries that have used the tool and shared their data. When shorter and longer regimens are replaced with BPaL/BPaLM, the savings per patient treated in Pakistan, the Philippines, South Africa, and Ukraine are $746, $478, $757, and $2,636, respectively. An increased number of patients would be successfully treated with BPaL/BPaLM regimens, with 411, 1,025, 1,371 and 829 lives saved and 20,179, 27,443, 33,384 and 21,924 DALYs averted annually in the four countries, respectively. CONCLUSION: Through BPaL/BPaLM regimens, drug-resistant TB treatment has become more effective, shorter, less burdensome for patients, cheaper for both health systems and patients, and saves more lives.